BeCAPTCHA-Mouse: Synthetic mouse trajectories and improved bot detection. (July 2022) - Acien, Alejandro; Morales, Aythami; Fierrez, Julian; Vera-Rodriguez, Ruben
Highlights: Two novel methodologies for mouse trajectory synthesis. A new bot detection algorithm based on neuromotor modeling of mouse trajectories Improved modeling of mouse dynamics based on real and synthesized samples. Public benchmark for research in bot detection and other mouse-based HCI applications. Abstract: We first study the suitability of behavioral biometrics to distinguish between computers and humans, commonly named as bot detection. We then present BeCAPTCHA-Mouse, a bot detector based on: i) a neuromotor model of mouse dynamics to obtain a novel feature set for the classification of human and bot samples; and ii) a learning framework involving real and synthetically generated mouse trajectories. We propose two new mouse trajectory synthesis methods for generating realistic data: a) a function-based method based on heuristic functions, and b) a data-driven method based on Generative Adversarial Networks (GANs) in which a Generator synthesizes human-like trajectories from a Gaussian noise input. Experiments are conducted on a new testbed also introduced here and available in GitHub: BeCAPTCHA-Mouse Benchmark; useful for research in bot detection and other mouse-based HCI applications. Our benchmark data consists of 15, 000 mouse trajectories including real data from 58 users and bot data with various levels of realism. Our experiments show that BeCAPTCHA-Mouse is able to detect bot trajectories of high realism with 93 % of accuracy in average using only one mouse trajectory. When our approach is fused with state-of-the-art mouse dynamic features, the bot detection accuracy increases relatively by more than 36 %, proving that mouse-based bot detection is a fast, easy, and reliable tool to complement traditional CAPTCHA systems.